In-Air Electron Streaming Effect for Esophageal Cancer Radiotherapy With a 1.5 T Perpendicular Magnetic Field: A Treatment Planning Study - Liu, Hongdong (Front Oncol, 2020)
PURPOSE: To investigate the in-air out-of-field electron streaming effect (ESE) for esophageal cancer radiotherapy in the presence of 1.5 T perpendicular magnetic field. METHODS: Ten esophageal cancer patients treated with conventional Linac were retrospectively enrolled into a cohort of this study, with the prescription of 4,400 cGy/20 fx. All cases received IMRT replanning using Elekta Unity MR-Linac specified Monaco system, denoted as primary plan. To visualize the in-air dose outside the body in Monaco system, an auxiliary structure was created by extending the external structure. For each case, another comparable plan with no magnetic field was created using the same planning parameters. The plan was also recalculated by placing a bolus upon the neck and chin area to investigate its shielding effect for ESE. Dosimetric evaluations of the out-of-field neck and chin skin area and statistical analysis for these plans were then performed. RESULTS: Out-of-field ESE was also observed in esophageal cancer treatment planning under 1.5 T magnetic field, while totally absent for plans with no magnetic field. On average, the maximum dose to the neck and chin skin area of the primary plan (657.92 ± 69.07 cGy) was higher than that of plan with no magnetic field (281.78 ± 36.59 cGy, p = 0.005) and plan with bolus (398.43 ± 69.19 cGy, p = 0.007). DVH metrics D(1cc) (the minimum dose to 1 cc volume) of the neck and chin skin for primary plan was 382.06 ± 44.14 cGy, which can be reduced to 212.42 ± 23.65 cGy by using the 1 cm bolus (with p = 0.005), even lower than the plan without magnetic field (214.45 ± 23.82, p = 0.005). No statistically significant difference of the neck and chin skin dose between the plan with bolus and plan with no magnetic field was observed (all with p > 0.05). CONCLUSION: For MRI guided esophageal cancer radiotherapy, a relatively high out-of-field neck and chin skin doses will be introduced by ESE in the presence of magnetic field. It is therefore recommended to take this into account during the planning phase. Adding bolus could effectively reduce the ESE dose contributions, achieve the shielding effect almost equivalent to the scenario with no magnetic field. Further explorations of measurement verifications for the ESE dose distributions are required.